The Wisconsin Frontier - Wyman, Mark (Book collections on Project MUSE., 1998)
By 1900 an era was rapidly passing, leaving Wisconsin's peoples with traditions of optimism and self-government, but confronting them also with tangled cutover lands and game scarcities that were a legacy of the settlers' belief in the inexhaustible resources of the frontier.